Changes in arterial blood vessels and VEGF and Ang‐1 expression in pregnant and non‐pregnant yak uterine caruncle. Issue 12 (6th September 2022) - Long, Min; Cui, Yan; Pang, Xin; Wang, Biao; He, Junfeng; Zhang, Qian; Yu, Sijiu; Bai, Xuefeng
Abstract: We investigated the structural features of arterial blood vessels in yak uterine caruncle and the effects of the expression of vascular regulation‐related factors on angiogenesis in pregnant and non‐pregnant yak uterus. Three‐dimensional specimens of the uterine artery of non‐pregnant and pregnant yaks were produced to observe and measure the distribution characteristics and number of arterial vessels in the uterus and caruncle in the two periods. The uterine caruncle structure was observed and analysed by haematoxylin–eosin staining. The expression features of vascular endothelial growth factor (VEGF) and angiopoietin‐1 (Ang‐1) in the uterine caruncle were detected with immunohistochemistry, quantitative real‐time PCR (qRT‐PCR) and western blotting. The length and number of blood vessels in the caruncle were increased, the degree of curvature was decreased, and the folding was more complicated during pregnancy as compared with that during non‐pregnancy. The immunohistochemical results demonstrated that VEGF and Ang‐1 were mainly expressed strongly in the mucosal epithelial cytoplasm. The glandular lumen of the uterine gland, lymphocytes and the media and adventitia of blood vessels are widely distributed, and they are all positive. VEGF and Ang‐1 mRNA and protein levels were highest in pregnancy, followed by that in the luteal phase and in the follicular phase, and three stages were significantly different ( p  < .05). These findings provide an anatomical reference and theoretical basis for improving the diagnosis and treatment of yak reproductive disorders and other diseases in high‐altitude and low‐oxygen environments.